Aplicación del control interno y el cumplimiento de las funciones del personal en la gerencia y administración de la Municipalidad Provincial de Maynas, 2019 - Benaún Gárate, Ana María (2021)
The purpose of this work was to determine the relationship between internal control and the fulfillment of the functions of the personnel in the Provincial Municipality of Maynas, year 2019; this being a descriptive-correlational study and non-experimental design, whose study sample was made up of 67 workers, in addition, having used the survey as a technique and the questionnaire as an instrument for data collection, and applied to the sample points It has been concluded that the application of internal control in the MPM is poor, because there is minimal evidence of the entity's commitment to develop control activities, in addition that the risks are not being properly assessed, which often does not allow that the activities are programmed correctly, and also the deficiencies in the information and communication are a determining factor to establish the responsibility, objectives and goals of the activities of control and supervision of the same. On the other hand, it is determined that the fulfillment of the functions of the MPM staff is deficient, since in a large extent the staff has difficulties in demonstrating that they have sufficient capacity to adequately develop their work, so that, at least, the contribution is the achievement of the institutional objectives. Finally, it is determined that there is a significant relationship between internal control and the fulfillment of the functions of the personnel in the MPM, which is contrasted with the correlation coefficient of 0.928 according to the Spearman Rho statistic, and a degree of significance of 0.000.